Beyond the needle: How nonsurgical management transforms foot and ankle ability in male footballers with posterior ankle impingement- a longitudinal study - Gupta, Jyoti (2024)
PurposePosterior ankle Impingement (PAI) is a condition commonly affecting athletes and individuals engaged in activities involving repetitive ankle plantar flexion. This study aimed to evaluate the impact of nonsurgical management, excluding corticosteroid injections, on the functional outcomes of football players diagnosed with PAI. Materials and methodsTwenty male football Players between age group of 18–30 years, clinically diagnosed of PAI, were included in this longitudinal study. Nonsurgical management was implemented over 8 weeks, including exercises. Players were assessed for pain, tenderness, range of motion(ROM), Foot and Ankle Ability Measure (FAAM), vertical and broad jump height at baseline, after 4 weeks and 8 weeks. ResultsSignificant improvements were observed in pain levels (p < 0.001), tenderness (p < 0.001), ROM (p < 0.001), and functional abilities measured by FAAM ADL (p < 0.001) and Sports subscales (p < 0.001) after 8 weeks of nonsurgical management. Horizontal jump performance significantly improved (p = 0.02), while vertical jump did not (p = 0.15) after 8 weeks. Tenderness and ROM showed significant changes after 4 and 8 weeks. The FAAM% score significantly increased (p < 0.001) after 8 weeks, reflecting enhanced overall functional ability. ConclusionsNonsurgical management of 8 weeks is an effective approach for ameliorating symptoms and enhancing functionality in football players with PAI as compared to 4 weeks.